Nephroprotective Effect of Ethanolic Extract of Balakka (Phyllanthus emblica L.) on Rats Induced Ethylene Glycol and Ammonium Chloride - Girsang, Ermi; Halima, Piyanto; Nasution, Ali Napiah; Lister, I nyoman Ehrich; Lie, Sukirman (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
The kidneys are a pair of symmetrical organs that function to filter the blood and are located in the retroperitoneal region on the posterior wall of the abdomen. The kidneys are drained about 25% of cardiac output. Kidney damage due to the accumulation of kidney stones can be caused by ethylene glycol substances to form calcium oxalate crystals (CaC2O4). This crystal is common in urine specimens even in healthy animals. Crystal formation can be accelerated by the administration of ammonium chloride. This study aims to determine the nephroprotective effects of balakka ethanol extract to reduce creatinine and urea levels in rats induced by ethylene glycol and ammonium chloride. The results showed that the balakka ethanol extract with a dose variation of 50 mg/kg body weight, 100 mg/kg body weight, and 150 mg/kg body weight had nephroprotective activity in rats that had been induced by ethylene glycol and ammonium chloride. Where the induction group had the largest serum creatinine mean of 1.43 mg/dl. The EEB treatment group dose of 50 mg / kgBB had a serum creatinine value of 1.01 mg / dl. The EEB treatment group dose of 100 mg / kgBB had a serum value of 0.91 mg / dl. The balakka ethanol extract treatment group dose of 150 mg / kgBB had a serum value of 0.73 mg / dl. The induction group had the largest serum urea serum of 76.56 mg/dl. EEB treatment group dose of 50 mg / kgBB had serum urea value of 63.36 mg / dl. The EEB treatment group dose of 100 mg / kgBB had a serum urea value of 49.73 mg / dl. The balakka ethanol extract treatment group dose of 150 mg / kgBB had a serum urea value of 49.90 mg / dl. Key Word : ureum, creatine, kidney.